Outsourcing as an Alternative for Higher Education Financing (HEF) in Nigeria: The Case of Adamawa State University Mubi, Gombe State University and Taraba State University, Nigeria - Mohammed Danjuma; Sani Ahmed Yauta; Musa Jerry (European Scientific Journal, ESJ, 2018)
Socio-political and economic issues relating to financing higher education is broadly deliberated and debated subject in many public mediums and academic gatherings in Nigeria, for over a decade to date. Altogether those deliberations and debates are grounded virtually on two basic principles of, financing adequacy and equitability. Inadequacy of education financing is blamed for the deterioration in the quality of education. Furthermore, inequitable resource allocation between federal and State universities in Nigeria forms part of the key issue in accomplishing efficiency of resource utilization which is missing in academic literatures addressing higher education financing in Nigeria. In the context of Nigeria, considering the practical experiences, especially in the operational mechanism of financing of Higher education, transparency and corruptions became a syndrome that ravishes the educational system. This study focuses on sources of higher education finance and the relative contribution of each source to educational development of the nation. At the same time, implications of the present financing mechanism on parity and efficiency of higher education if Outsourcing is introduced as an alternative source of funding in the subsector. This study examines the matters relating to Higher Education Financing at three levels; financial allocation, resources allocation and education output distribution. This study is exploratory cross sectional survey and collects both primary and secondary data from relevant literatures available. The study revealed that outsourcing is a means of Internally Generated Revenue (IGR) in higher institution and therefore serve as alternative means of financing higher education in broad and university education in particular. Therefore, this study recommends formal incorporation of outsourcing in financing of university education in Nigeria.